2015
DOI: 10.2139/ssrn.2648129
|View full text |Cite
|
Sign up to set email alerts
|

Bank Level and Country Level Determinants of Bank Capital Structure and Funding Sources

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In summary, the minimum capital requirement by the central bank, support by the central bank as a last resort and insurance of deposits constitute other reasons that could replace the requirement of tangible assets as collateral. These results are in line with the findings of Baltacı and Ayaydın (2014), Sheikh and Qureshi (2017) and Hoque and Pour (2018).…”
Section: Discussion Of Empirical Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In summary, the minimum capital requirement by the central bank, support by the central bank as a last resort and insurance of deposits constitute other reasons that could replace the requirement of tangible assets as collateral. These results are in line with the findings of Baltacı and Ayaydın (2014), Sheikh and Qureshi (2017) and Hoque and Pour (2018).…”
Section: Discussion Of Empirical Resultssupporting
confidence: 92%
“…This mitigates the agency problems between shareholders and managers that arise because of managerial opportunism or shirking. Several studies concluded that profitability is negatively related to leverage, which endorses the assumptions of pecking order theory, including Titman and Wessels (1988), Rajan and Zingales (1995), Wald (1999), Booth et al (2001), Viviani (2008), Sheikh and Wang (2013), Sheikh and Qureshi (2017) and Hoque and Pour (2018).…”
Section: Literature Reviewmentioning
confidence: 62%
See 1 more Smart Citation
“…It is shown that liquidity risk has reverse impacts on bank performance in a market‐based financial system. Hoque and Kashefi Pour (2018) examine the determinants of capital structure and funding sources of 347 large global banks between 1998 and 2016 from 57 countries around the world. They find that the capital structure of banks is affected by market forces as well as it evolves as a result of capital regulatory framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Funding Sources for Banks Funds management in banks (Borisoff Alexander & Andrew Compton, 2015), commonly referred to as Manajemen Pasiva Bank in Indonesia, is very important given that banks are primarily funded (more than 90%) by parties outside the bank owners (Mandala, 2004;Hoque, Hafiz and Kashefi-Pour, Eilnaz, 2015). The bulk of bank funding sources come from public savings (Third-Party Funds) in the form of demand deposits, savings and deposits.…”
Section: Consistent Withmentioning
confidence: 99%